1979
DOI: 10.1029/jc084ic10p06307
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of lightning return stroke electric and magnetic fields from simultaneous two‐station measurements

Abstract: We present a characterization of Florida lightning return stroke electric and magnetic fields derived from simultaneous measurements of the fields at two separate stations, one station being within 15 km of the lightning, the other at either about 50 or 200 km from the lightning. We give (1) examples of correlated wave forms, (2) typical first and subsequent stroke wave forms over the distance range 1.0–200 km, and (3) the following statistical data from which the typical wave forms were derived: for electric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
154
1
6

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 252 publications
(183 citation statements)
references
References 15 publications
22
154
1
6
Order By: Relevance
“…Also, it has been reported by Lin et al [1979] that the distance-normalized magnitude of vertical electric field is reduced to about 90% and 80% after propagating 50 and 200 km, respectively. Further, it has been reported by Uman et al [1976] that the mean 10-90% risetime of observed vertical electric field is increased by about 1 μs after propagation over 200 km of land with conductivity of 1.4 to 2.8 mS/m.…”
Section: 1002/2015jd023245mentioning
confidence: 99%
“…Also, it has been reported by Lin et al [1979] that the distance-normalized magnitude of vertical electric field is reduced to about 90% and 80% after propagating 50 and 200 km, respectively. Further, it has been reported by Uman et al [1976] that the mean 10-90% risetime of observed vertical electric field is increased by about 1 μs after propagation over 200 km of land with conductivity of 1.4 to 2.8 mS/m.…”
Section: 1002/2015jd023245mentioning
confidence: 99%
“…At these distances, the tortuous model is also able to reproduce another interesting feature of close electric fields, namely a very fast transition in a time interval of a few hundreds of nanoseconds towards a "first peak", followed by a slower increase of the field [38]. The first peak is due to the field radiation component, it is almost independent of the observation point and can be now more easily identified, if compared to closer waveforms.…”
Section: Electric Field E(t)mentioning
confidence: 65%
“…6, are able to reproduce these typical characteristics. As an example, in The field evolution presents both the sharp increase and "humps", but not the "slow front" characteristic; this is probably due to the presence of an upward connecting leader [38] which, as discussed above, is not accounted in the present model, but is typical for triggered channels.…”
Section: Electric Field E(t)mentioning
confidence: 95%
See 1 more Smart Citation
“…A typical CG lightning flash is composed by more than one discharge known as return stroke. These individual discharges have a duration of tens of microseconds and they are usually separated in time from 20 ms to 100 ms [29]. The typical waveforms for the electric fields produced by the first return stroke (FRS) and the subsequent return strokes (SRS) that compose a flash are shown in Fig.…”
Section: Typical Waveforms Of Lef Signalsmentioning
confidence: 99%